Psychophysiological reactivity in couples during a marital interaction task - Coutinho, J. (2018)
The ability to regulate our own physiological arousal when dealing with the emotional expression of our partner is crucial for satisfactory and stable intimate relationships. In previous physiological studies of marital interactions, researchers have found greater levels of psychophysiological arousal for members of the couple in conflictual interactions in comparison with positive interactions. Past researchers have established that intense and prolonged autonomic and neuroendocrine arousal during marital conflict can have negative consequences for mental and physical health. In this study we examined the physiological reactivity, as measured by skin conductance level, heart rate and cortisol levels, from both partners during a couple's interaction task consisting of a structured conversation about positive and negative aspects of their relationship. Participants were thirty-two heterosexual couples (N = 64) in a committed monogamous relationship with a minimum duration of one year. We found higher heart rate and cortisol levels during negative interaction condition when compared with the positive condition. Skin conductance was higher in the positive interaction condition, when compared with the negative interaction condition. In addition, we found a significant negative association between heart rate variability and autonomic arousal evoked by the interaction task. The implications of these findings for the effects of marital strain on health as well as for the design of risk-reducing interventions, namely biofeedback are discussed.